Chlorin, phthalocyanine, and porphyrin types derivatives in phototreatment of cutaneous manifestations: A review - De Annunzio, Sarah Raquel [UNESP]; Costa, Natalia Caroline Silva [UNESP]; Graminha, Márcia A. S. [UNESP]; Fontana, Carla Raquel [UNESP]; Mezzina, Rafaela Dalbello [UNESP] (MDPI, 2019)
Recent scientific research has shown the use of chlorin, phthalocyanines, and porphyrins derivatives as photosensitizers in photodynamic therapy in the treatment of various pathologies, including some of the major skin diseases. Thus, the main goal of this critical review is to catalog the papers that used these photosensitizers in the treatment of acne vulgaris, psoriasis, papillomavirus infections, cutaneous leishmaniasis, and skin rejuvenation, and to explore the photodynamic therapy mechanisms against these conditions alongside their clinical benefits.
Keywords: Chlorins; Photodynamic therapy; Phthalocyanines; Porphyrins; Skin diseases; Skin rejuvenation